Early Childhood Nutrition Knowledge of Caregivers in Tanzania - Moxley, Victor B.A.; Graul, Maggie F.; Stoneking, Nathan; Hale, Cecily; Torres, Scott; Linehan, Mary; Dobies, Kerry Ann; Mulokozi, Generose; Hoj, Taylor H.; Crookston, Benjamin T.; Hall, P. Cougar; West, Joshua H. (International Journal of Child Health and Nutrition, 2019)
Childhood stunting is a pressing health issue in Tanzania and results from chronic infections and inadequate nutrition. Educating caregivers on the nutritional determinants, their consequences, and appropriate solutions may improve nutrition-related practices among caregivers in Tanzania. The purpose of this study was to identify factors associated with Tanzanian caregivers’ knowledge of childhood nutrition practices. Data for this study came from a cross-sectional survey of 4,095 caregivers of children under 24 months living in the Geita, Kagera, Kigoma, Mwanza, and Shinyanga regions of Tanzania. Complete responses relating to demographic and socioeconomic factors, media exposure, and early childhood nutrition knowledge were analyzed using multiple linear regression modeling techniques. Caregivers’ knowledge concerning proper early childhood nutrition practices was found to be significantly related to using a mobile banking account (p<.0001), owning a working radio with batteries (p<.0001), having watched television recently (p<.0001), residing in a southern lake region (p<.0001), affiliating with a Christian faith (p=0.0027), having more children under the age of 5 (p=0.0005), having received advice on maternal nutrition before pregnancy (p<.0001) and having received advice from a community health worker (p=0.0184). Living in a rural environment (p<.0001) and speaking a non-mainstream language (p<0.05) were significantly associated with decreased knowledge. The influences of media and technology, socio-demographic factors and traditional health education may be important in the development of accurate childhood nutrition knowledge among caregivers. These factors may be targeted for future community health worker efforts with vulnerable populations in Tanzania to prevent stunting.